Inclusion, characteristics and outcomes of people requiring palliative care in studies of non-pharmacological interventions for delirium: A systematic review. (September 2019) - Hosie, Annmarie; Siddiqi, Najma; Featherstone, Imogen; Johnson, Miriam; Lawlor, Peter G; Bush, Shirley H; Amgarth-Duff, Ingrid; Edwards, Layla; Cheah, Seong Leang; Phillips, Jane; Agar, Meera
Background: Delirium is common, distressing, serious and under-researched in specialist palliative care settings. Objectives: To examine whether people requiring palliative care were included in non-pharmacological delirium intervention studies in inpatient settings, how they were characterised and what their outcomes were. Design: Systematic review (PROSPERO 2017 CRD42017062178). Data sources: Systematic search in March 2017 for non-pharmacological delirium intervention studies in adult inpatients. Database search terms were 'delirium', 'hospitalisation', 'inpatient', 'palliative care', 'hospice', 'critical care' and 'geriatrics'. Scottish Intercollegiate Guidelines Network methodological checklists guided risk of bias assessment. Results: The 29 included studies were conducted between 1994 and 2015 in diverse settings in 15 countries (9136 participants, mean age = 76.5 years ( SD  = 8.1), 56% women). Most studies tested multicomponent interventions ( n  = 26) to prevent delirium ( n  = 19). Three-quarters of the 29 included studies ( n  = 22) excluded various groups of people requiring palliative care; however, inclusion criteria, participant diagnoses, illness severity and mortality indicated their presence in almost all studies ( n  = 26). Of these, 21 studies did not characterise participants requiring palliative care or report their specific outcomes (72%), four reported outcomes for older people with frailty, dementia, cancer and comorbidities, and one was explicitly focused on people receiving palliative care. Study heterogeneity and limitations precluded definitive determination of intervention effectiveness and only allowed interpretations of feasibility for people requiring palliative care. Acceptability outcomes (intervention adverse events and patients' subjective experience) were rarely reported overall. Conclusion: Non-pharmacological delirium interventions have frequently excluded and under-characterised people requiring palliative care and infrequently reported their outcomes.